2007
DOI: 10.1016/j.asr.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the IRI model using CHAMP observations in polar and equatorial regions

Abstract: This study compares the electron density and temperature observed by the CHAMP satellite and those predicted by the International Reference Ionosphere (IRI) model.The comparison has revealed a general agreement between CHAMP and IRI in the seasonal variation of the electron density and temperature. However, in polar regions, the model tends to overestimate the electron density and underestimate the electron temperature. In addition, the CHAMP observes a weaker winter anomaly in the southern hemisphere than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Similar phenomenon was found to occur at Port Lockroy (65.8°S, 63.5°W) [ Rastogi , 1960] and also in the northern hemisphere at Millstone Hill (42.6°N, 71.5°W) [ Evans , 1965]. Global observations from the CHAMP satellite showed unusual diurnal variations of Ne in summer midlatitudes in both hemispheres [ Liu et al , 2007b]. Recently, detailed climatology of the WSA has been reported based on modern satellite observations [ Horvath and Lovell , 2009; Lin et al , 2009; Jee et al , 2009; He et al , 2009, and references therein].…”
Section: Introductionsupporting
confidence: 66%
“…Similar phenomenon was found to occur at Port Lockroy (65.8°S, 63.5°W) [ Rastogi , 1960] and also in the northern hemisphere at Millstone Hill (42.6°N, 71.5°W) [ Evans , 1965]. Global observations from the CHAMP satellite showed unusual diurnal variations of Ne in summer midlatitudes in both hemispheres [ Liu et al , 2007b]. Recently, detailed climatology of the WSA has been reported based on modern satellite observations [ Horvath and Lovell , 2009; Lin et al , 2009; Jee et al , 2009; He et al , 2009, and references therein].…”
Section: Introductionsupporting
confidence: 66%
“…A comparison between the IRI 2001 model and data from the CHAMP satellite showed general agreement between CHAMP data and the IRI model in the seasonal variation of the electron density and temperature, with some exceptions (Liu et al 2007). A later study performed a comparison with Slant Total Electron Content (STEC) data and found that IRI2007 is much improved compared to IRI2001 (Coïsson et al 2008).…”
Section: Stec From Pre-computed Ionospheric Datamentioning
confidence: 93%
“…The root mean square (RMS) difference of electron density was about 10 3 cm À3 above 150 km for the horizontally stratified ionosphere (Schreiner et al, 2007). In addition, CHAMP uses a planar Langmuir probe (PLP) to perform in situ measurements of ionospheric electron density and temperature every 15 s. The accuracy of the PLP measurements is within 10% (Liu et al, 2007).…”
Section: Datamentioning
confidence: 99%